Positive strengths of personality for Nineveh governorate players clubs of Football - Ali Al-Heyali; Muayad Hassoo (مجلة الرافدين للعلوم الرياضية, 2022)
The goal of the research is to construct a positive strengths of personality for Nineveh governorate players clubs of   football, and the researchers used the descriptive approach to its  suitability with the nature of the research .The community of the research were from first and second class rank in Nineveh's football season (2020,2021) , the players were about  (595) players distributed on (32) universities supported by football minor federation in Nineveh to check that  the search creation ,sample construction included (19) clubs in a random manner of  the (425)-year-old community, which ranged(%71.42) of the communities research. The researchers received ( 336 ) valid statistical analysis and (%92.5) of the main construction sample as well as excluding (29) players for lack of answers to the scales of the scale  according with the scientific basis of the methods of measurements . The researcher used (Spss  )as well as ( excel version 2016) (the percentage, , the arithmetic mean, the standard deviation, the simple correlating coefficient (Person), T-test , difference analysis), in the light of the statistical Processing, the researchers came to conclude that, the positive strength scale has been proved  a high effectiveness for personality  as to construct it in an  accurate scientific specifications.